Cardiac troponin elevation pattern in patients undergoing a primary percutaneous coronary intervention for ST-segment elevation myocardial infarction: characterization and relationship with cardiovascular events during hospitalization. Issue 6 (September 2015) - Buber, Jonathan; Laish-Farkash, Avishag; Koren-Morag, Nira; Fefer, Paul; Segev, Amit; Hod, Hanoch; Matetzky, Shlomi
Abstract : Hypothesis: We aimed to describe the kinetics and associated prognostic implications of the cardiac troponin release curve after a primary percutaneous coronary intervention (PPCI) in patients presenting with ST-segment elevation myocardial infarction (STEMI). Patients and methods: We prospectively determined, in a prespecified timely manner, serial cardiac troponin I levels and obtained clinical, ECG, and echocardiographic data from 175 consecutive patients hospitalized with STEMI who underwent PPCI. The median peak troponin levels and time until troponin peaking were determined. Results: The troponin elevation curve following PPCI was single peaked, with a median value measuring 715 times the upper normal limit and a median peaking time of 8 h. Later-peaking troponin levels were associated with a TIMI flow grade of 0/1 at the initiation of angiography and with lack of at least 70% regression in the ST-elevation on the first post-PPCI ECG. Higher peak values were similarly associated with these two parameters as well as with a lower blush score and with distal embolization during PPCI. Both higher peak values and later peaking of troponin were associated independently with higher occurrence of the combined adverse cardiovascular event outcomes consisting of death, congestive heart failure, and recurrent infarction. Conclusion: The cardiac troponin elevation curve following PPCI for STEMI shows a single peak and is affected by the adequacy of myocardial reperfusion. This method can serve as a simple surrogate for risk stratification of patients with STEMI who undergo PPCI.